Feasibility Analysis of Weather Observation Equipment at Meteorological Stations in Supporting Flight Safety at Rahadi Oesman Ketapang Airport - Griselda Ardelia; Awan Awan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Weather is one of the main factors for the world of aviation in supporting flight safety. Because aircraft are included in the mode of transportation that occurs in the atmosphere, so it greatly influences the operation of aircraft. Bad weather can cause flight schedules to change suddenly, causing delays and threatening flight safety. Therefore it is necessary to carry out weather observations, these observations are carried out by an agency called the Meteorological Station. The implementation of weather observations requires meteorological tools, these tools are divided into two types, namely conventional tools and automatic tools. What must be considered from the weather observation tool at the Rahadi Oesman Ketapang Meteorological Station is its feasibility. Therefore, this study aims to determine the condition of weather observation tools in supporting flight safety and to determine the obstacles experienced by the Ketapang Meteorological Station and the handling of these obstacles. This study used qualitative research methods. The data needed is primary data in the form of interviews and observations. And secondary data documentation in the form of data obtained from the Rahadi Oesman Ketapang Meteorological Station, in addition to other data obtained through journals, articles, or previous research that has something to do with the research that researchers are doing. Data analysis techniques in this study used data reduction, data presentation and conclusion. Based on the data obtained from this study, the tools used at the Rahadi Oesman Ketapang Meteorological Station are operationally feasible, as evidenced by the results in the latest calibration certificate. However, after the calibration was carried out the following month, several obstacles were found, such as conventional and automatic tools that had problems, such as broken glass thermometers, sensors and networks on AWOS and AWS, frequent interruptions occurred which prevented data transmission, and the rain gauge was damaged. Then constrained by a very minimal supply of spare parts, so it is necessary to increase the spare parts.